The replication initiator protein of plasmid pSC101 is a transcriptional repressor of its own cistron. - Vocke, C (1985)
The plasmid-encoded replication initiator protein of pSC101 specifically repressed initiation of transcription of its own cistron from its natural promoter. Addition of the purified initiator had little or no visible effect on transcription initiated from a heterologous promoter. DNase protection experiments revealed that the RNA polymerase recognition sequence was overlapped by the initiator protein recognition sequences, which are vicinal to the replication origin. Using the labeled promoter sequence, we have performed competitive DNase protection experiments in two ways: by adding RNA polymerase and initiator protein simultaneously or by sequentially adding first RNA polymerase and then initiator protein to the DNase reaction mixture. The RNA polymerase protection pattern was recessive to that of the initiator regardless of whether the two proteins were added simultaneously or sequentially. This observation suggests that the mechanism of autoregulation is due to competition of the two proteins for the sequences in and around the promoter region. Furthermore, the sequential addition experiments raise the possibility of displacement of RNA polymerase from the promoter by the initiator protein.